Evaluation of gram-chromotrope kinyoun staining technique: its effectiveness in detecting microsporidial spores in fecal specimens - Salleh, F.M.; Al-Mekhlafi, A.M.; Nordin, A.; Yasin, A.M.; Al-Mekhlafi, H.M.; Moktar, N. (2011)
This study was conducted to evaluate the modification of the usual Gram-chromotrope staining technique developed in-house known as Gram-chromotrope Kinyoun (GCK) in comparison with the Weber Modified Trichrome (WMT) staining technique; as the reference technique. Two hundred and ninety fecal specimens received by the Microbiology Diagnostic Laboratory of Hospital Universiti Kebangsaan Malaysia were examined for the presence of microsporidial spores. The sensitivity and specificity of GCK compared to the reference technique were 98 and 98.3, respectively. The positive and negative predictive values were 92.5 and 99.6, respectively. The agreement between the reference technique and the GCK staining technique was statistically significant by Kappa statistics (K = 0.941, P < 0.001). It is concluded that the GCK staining technique has high sensitivity and specificity in the detection of microsporidial spores in fecal specimens. Hence, it is recommended to be used in the diagnosis of intestinal microsporidiosis. (C) 2011 Elsevier Inc. All rights reserved.